2022
DOI: 10.3390/ijerph192416496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19-Related Social Isolation on Behavioral Outcomes in Young Adults Residing in Northern Italy

Abstract: Social isolation affects our emotions, behavior and interactions. Worldwide, individuals experienced prolonged periods of isolation during the first wave of the COVID-19 pandemic when authorities-imposed restrictions to reduce the spread of the virus. In this study, we investigated the effects of social isolation on emotional and behavioral outcomes in young adults from Lombardy, Italy, a global hotspot of COVID-19. We leveraged baseline (pre-social isolation) and follow-up (mid- or post-isolation) data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
“…In this respect, the association between younger age and lower levels of mental health during the COVID-19 pandemic has been documented. In particular, young adults have been found to experience high rates of loneliness, anxious and depressive symptoms, stress, and sleep disturbances [24][25][26][27][28][29][30][31][32][33][34][35][36]. Whether these changes were associated with a parallel change in AD consumption needs to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Outside this context of COVID pandemic, singlehood has been already shown to have a considerable impact on the psychological health of individuals in the general population [ 2 ]. In individuals living alone, the lockdown situation obviously aggravated this isolation by reducing or completely eliminating the interactions which were previously maintained through working activities [ 31 , 37 ]. The absence of a close partner with whom the patient can share his/her impressions, routines of daily life, hobbies and can discuss the information received through the media appears to be particularly deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID‐19 period, Italian studies compared groups of different informants and analyzed the impact of social isolation on behavior (Patrono et al, 2022). Our research was conducted over the same period, and it was analyzed that students perceived greater behavioral and emotional difficulties (assessed using the SDQ) than faced by parents and teachers.…”
Section: Discussionmentioning
confidence: 99%